2007
DOI: 10.1097/01.aids.0000279714.60935.a2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact and cost-effectiveness of antiretroviral therapy in India: starting criteria and second-line therapy

Abstract: In India, antiretroviral therapy will lead to major survival benefits and is cost-effective by World Health Organization criteria. The availability of second-line regimens will further increase survival, but their cost-effectiveness depends on their relative cost compared with first-line regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 27 publications
0
47
1
Order By: Relevance
“…Investigators in Cape Town, South Africa, found that ART was reasonably cost-effective for South African patients and that there were incremental benefits from starting ART at each successively higher CD4 threshold (1350 cells/mL vs. 200-350 cells/mL or !200 cells/mL) [26]. The Cost-Effectiveness of Preventing AIDS Complications group developed models for Cote d'Ivoire [27], India [28], and the eastern Caribbean [29] that yielded similar conclusions.…”
Section: Cost-effectivenessmentioning
confidence: 94%
“…Investigators in Cape Town, South Africa, found that ART was reasonably cost-effective for South African patients and that there were incremental benefits from starting ART at each successively higher CD4 threshold (1350 cells/mL vs. 200-350 cells/mL or !200 cells/mL) [26]. The Cost-Effectiveness of Preventing AIDS Complications group developed models for Cote d'Ivoire [27], India [28], and the eastern Caribbean [29] that yielded similar conclusions.…”
Section: Cost-effectivenessmentioning
confidence: 94%
“…Eventually, each monitoring method was found to improve patient outcomes and to be cost-effective [17][18][19][20][21][22]. As the challenges of vaccine development became increasingly apparent, researchers found that HAART coupled with behavioral strategies was perhaps the only real tool to stem the tide of the epidemic for a long time [23][24][25][26]. Therefore, understanding and preventing drug resistance wherever HAART is used is essential to maintaining the value of HAART in the future.…”
mentioning
confidence: 99%
“…1 The emergence of HIV-2 infection in this country was documented in the early 1990s and was believed to have then spread in parallel with HIV-1 infection, albeit at a much lower incidence rate. The prevalent HIV-2 subtype A was reported in various regions of the country, including HIV-1 and HIV-2 dual infections.…”
mentioning
confidence: 99%